2016
DOI: 10.1016/j.clinph.2015.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Multi-scale analysis of neural activity in humans: Implications for micro-scale electrocorticography

Abstract: Recorded with appropriately scaled electrodes and grids, field potentials expose a more detailed representation of cortical network activity, enabling advanced analyses of cortical pathology and demanding applications such as brain-computer interfaces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
74
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(83 citation statements)
references
References 82 publications
9
74
0
Order By: Relevance
“…Bandwidths of around 60 Hz and 2nd order Butterworth filters offer a good compromise for our application. The frequency spectrum of spikes is usually invariant and does not exceed 3000 Hz (Rey et al, 2015; Kellis et al, 2016). In this work, we defined a frequency range of 100–2000 Hz for the signal analysis which allows to exclude low frequent background signals (below 100 Hz).…”
Section: Spiking Neural Network (Snn) Architecture For Spike Sortingmentioning
confidence: 99%
“…Bandwidths of around 60 Hz and 2nd order Butterworth filters offer a good compromise for our application. The frequency spectrum of spikes is usually invariant and does not exceed 3000 Hz (Rey et al, 2015; Kellis et al, 2016). In this work, we defined a frequency range of 100–2000 Hz for the signal analysis which allows to exclude low frequent background signals (below 100 Hz).…”
Section: Spiking Neural Network (Snn) Architecture For Spike Sortingmentioning
confidence: 99%
“…Until recently, ECoG electrodes were generally used to identify epileptogenic foci in clinical situations, using large electrodes that typically had a diameter of ~4 mm and an inter-electrode distance of ~10 mm. However, a large number of recent studies have employed methods with higher electrode density, higher channel counts, and smaller electrodes (Rubehn et al, 2009; Ledochowitsch et al, 2011; Matsuo et al, 2011; Toda et al, 2011; Viventi et al, 2011; Escabí et al, 2014; Castagnola et al, 2015; Kellis et al, 2015; Khodagholy et al, 2015; Hotson et al, 2016). While high-density ECoG recording seems to improve BMI performance, for instance, by enhancing naturalistic control of prosthetic arms, few studies have directly demonstrated the efficacy of this technique.…”
Section: Introductionmentioning
confidence: 99%
“…In most cases, these high density arrays have covered a very small area of cortex, and therefore large scale comparisons of shared signal in space have not been evaluated. Recently, correlations in the raw signal have been explored with respect to distance using a clinical ECoG array and a microwire ECoG array(Kellis et al, 2015). However, the measured signals from the microwire array are inherently different from those of the clinical array due to filtering effects of electrode size and shape(Kent & Grill, 2014; Lempka et al, 2011).…”
Section: Introductionmentioning
confidence: 99%